Cultural Semiotics of the Use of Jidur, Terbang, and Kendhang in Dolalak Dance: A Symbolic Analysis of Specific Instruments - Maria Magdalena Cita Hapsari; Adhitya Darmantho (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The musical instruments in Dolalak dance; jidur, terbang, and kendhang, have become the main subject in the attempt to understand the essence flowing within each musical call and dance vibration. The presence of these instruments is not merely as accompaniment, but rather imbues the space with profound meaning. Questions arise: Why were these instruments chosen? Are they related to cultural values or hidden beliefs? This research is structured with a descriptive qualitative approach. The use of jidur, terbang, and kendhang musical instruments in Dolalak dance in Purworejo goes beyond mere musical elements and physical movements. In this understanding, through Roland Barthes' conception of signifier and signified, it opens the way to delve into deeper meanings and symbolism inherent in each musical instrument. Every beat on jidur, terbang strike, or kendhang resonance not only produces sound but also carries messages containing cultural values, history, and the cultural identity of the Purworejo community.